Road Damage Analysis using Surface Distress Index (SDI) and Its Handling on Provincial Road Babat - Jombang (STA 7+000 - 12+500) - Prasodjo, Kevin Daffarial; Sholichin, Ibnu; Estikhamah, Fithri (CIVED, 2024)
The Babat - Jombang road is often traveled by highly loaded vehicles because there are large industries along this section. In addition, the road is damaged by weather and poor subgrade conditions. Thus, resulting in road damage that can interfere with user comfort. Therefore, road damage analysis research was conducted on Babat - Jombang Road (STA 7+000 - 12+500). Road damage analysis in this study using the SDI method. The SDI (Surface Distress Index) method is a road performance scale obtained from visual observations of road damage that occurs in the field. The SDI method is a method that produces an SDI value obtained from the percentage of crack area, crack width, number of holes per 100 m, and the depth of the ruts. From this research, the types of damage on Babat - Jombang Road (STA 7+000 - 12+500) are the hole damage area of 0.11%, longitudinal cracks of 12.05%, transverse cracks of 0.17%, edge cracks of 0.29%, crocodile skin cracks of 79, 66%, shoulder joint cracking by 0.0015%, ruts by 1.48%, bleeding by 1.1%, ravelling by 2.61%, surface layer flaking by 0.13%, patches by 0.26%, upheavel by 0.51%, shoving by 1.6%. Road condition assessment using SDI method shows 87.27% in good condition and 12.73% in moderate condition. Handling carried out is leveling, sealing, hot aggregate sprinkle, and patching holes.